Exploring the consequences of decentralization: has privatization of health services been the perceived effect of decentralization in Khartoum locality, Sudan? - Bandar Noory; Sara A. Hassanain; Benedikte Victoria Lindskog; Asma Elsony; Gunnar Aksel Bjune (BMC, 2020)
Abstract Background The health system of Sudan has experienced several forms of decentralization, as well as, a radical reform. Authority and governance of secondary and tertiary health facilities have been shifted from federal to state levels. Moreover, the provision of health care services have been moved from large federal tertiary level hospitals such as Khartoum Teaching Hospital (KTH) and Jafaar Ibnoaf Hospital (JIH), located in the center of Khartoum, to smaller district secondary hospitals like Ibrahim Malik (IBMH), which is located in the southern part of Khartoum. Exploring stakeholders' perceptions on this decentralisation implementation and its relevant consequences is vital in building an empirical benchmark for the improvement of health systems. Methods This study utilised a qualitative design which is comprised of in-depth interviews and qualitative content analysis with an inductive approach. The study was conducted between July and December 2015, and aimed at understanding the personal experiences and perceptions of stakeholders towards decentralisation enforcement and the implications on public health services, with a particular focus on the Khartoum locality. It involved community members residing in the Khartoum Locality, specifically in catchments area where hospital decentralisation was implemented, as well as, affiliated health workers and policymakers. Results The major finding suggested that privatisation of health services occurred after decentralisation. The study participants also highlighted that scrutiny and reduction of budgets allocated to health services led to an instantaneous enforcement of cost recovery user fee. Devolving KTH Khartoum Teaching and Jafar Ibnoaf Hospitals into peripherals with less. Capacity, was considered to be a plan to weaken public health services and outsource services to private sector. Another theme that was highlighted in hospitals included the profit-making aspect of the governmental sector in the form of drug supplying and profit-making retail. Conclusions A change in health services after the enforcement of decentralisation was illustrated. Moreover, the incapacitation of public health systems and empowerment of the privatisation concept was the prevailing perception among stakeholders. Having contextualised in-depth studies and policy analysis in line with the global liberalisation and adjustment programmes is crucial for any health sector reform in Sudan.